Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Efektivitas Kinerja Pegawai Pada Sekretariat DPRD Kota Makassar - Tasya; Akmal Umar; Dahlan (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2026)
Tasya, 2025. The Influence of Work Motivation and Job Satisfaction on the Effectiveness of the Performance of Employees at the Makassar City Council Secretariat, Thesis, Management Study Program, Indonesian Management College (STIMI) Yapmi Makassar. Supervised by AdvisorI, Mr. Akmal Umar, and Advisor II, Mr. Dahlan. This study aims to examine the influence of work motivation and job satisfaction on the effective performance of employees at the Makassar City Council office. The research method used is a quantitative method. The population in this study was 227 employees, from which population the Slovin formula was used to determine the number of samples used in the study, namely 69 employees. The data was analyzed using multiple linear regression tests with the help of Microsoft Excel and SPSS 27 programs. The results of the study showed that (1) work motivation has a positive and significant effect on the effectiveness of employee performance at the Makassar City DPRD Secretariat Office, (2) job satisfaction has a positive and significant effect on the effectiveness of employee performance at the Makassar City DPRD Secretariat Office, (3) work motivation and job satisfaction have a simultaneous effect on the effectiveness of employee performance at the Makassar City DPRD Secretariat Office.